PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PASAR DAN KINERJA PERUSAHAAN YANG TERDAPAT DI BURSA EFEK INDONESIA TAHUN 2010-2012 - Sari F. Siahaan; Haryanto Haryanto (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to examine the effect of intellectual capital to the market value and financial performance company. This study uses a model developed by Pulic Value Added Intellectual Coefficients (VAICTM). This study examines the effect of VAIC and the three components of intellectual capital capital employed (VACA), human capital (VAHU), structural capital (STVA) towards market value (MtBV) and the company’s financial performance return on asset (ROA), return on equity (ROE), and growth revenue (GR).Sampling method that’s used in this study is purposive sampling. Sample used in study is all company’s financial statements to Infrastructure, Utility and Transportation, issued by BEI (Indonesia Stock Exchange) during the period 2010-2012. This study uses a multiple linear regression test analysis. The result of the study shows that combined intellectual capital has no effect to market value. Yet, human capital affects the market value. Intellectual capital affect positively significant towards financial performance return on asset (ROA), return on equity (ROE), dan growth revenue (GR).